2014
DOI: 10.1016/s1474-4422(14)70194-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific population frequencies of cerebral β-amyloidosis and neurodegeneration among people with normal cognitive function aged 50–89 years: a cross-sectional study

Abstract: Summary Background As treatment of pre-clinical Alzheimer's disease (AD) becomes a focus of therapeutic intervention, observational research studies should recognize the overlap between imaging abnormalities associated with typical aging vs those associated with AD. Our objective was to characterize how typical aging and pre-clinical AD blend together with advancing age in terms of neurodegeneration and b-amyloidosis. Methods We measured age-specific frequencies of amyloidosis and neurodegeneration in 985 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
282
3
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 330 publications
(304 citation statements)
references
References 39 publications
17
282
3
2
Order By: Relevance
“…Basal ganglia may shrink by the age per se [49], or because of the disruption of their connections with the cerebral cortex caused by WMH and/or lacunae, or as a consequence of the age-related cortical thinning [50]. Although only speculative, given that a nonnegligible percentage of cognitively unimpaired elderly-old subjects have an increased Ab deposition [5][6][7][8], an additional contribution to subcortical atrophy could be caused by the retrograde transport of Ab along axonal membranes [51] to basal ganglia cell bodies. Interestingly, Ab deposition [52] and atrophy [53] have been described in the striatum of different Alzheimer disease (AD) mutation carriers and sporadic AD [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basal ganglia may shrink by the age per se [49], or because of the disruption of their connections with the cerebral cortex caused by WMH and/or lacunae, or as a consequence of the age-related cortical thinning [50]. Although only speculative, given that a nonnegligible percentage of cognitively unimpaired elderly-old subjects have an increased Ab deposition [5][6][7][8], an additional contribution to subcortical atrophy could be caused by the retrograde transport of Ab along axonal membranes [51] to basal ganglia cell bodies. Interestingly, Ab deposition [52] and atrophy [53] have been described in the striatum of different Alzheimer disease (AD) mutation carriers and sporadic AD [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…However, certain limitations of our study need to be addressed. Firstly, we acknowledge that four subgroups among cognitively normal subjects aged 50-89 years have been recently identified on the basis of various combination of imaging biomarkers of b-amyloidosis and neurodegeneration and that 43 % only of these subjects had normal AD biomarkers and no evidence of subtle cognitive impairment [8]. The normality of our cohort was ascertained solely on the basis of the medical history and of the cognitive and neurological evaluations, thus we do not know which subgroup our NCH subjects belong to.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, many people retain normal cogni tive function despite substantial amyloid burden. 8 Hence, the task force does not recommend amy loid imaging in people with normal cognitive function (Box 1). 7 However, some studies have found negative correlations between PiB and episodic memory in this group, whereas other studies found no differences across cognitive measures between PiB positive and PiB nega tive controls.…”
Section: What Are the Possible Harms?mentioning
confidence: 99%
“…Since until recently it was not possible to study in vivo brain changes associated with Alzheimer's pathology, previous research on word retrieval in normal cognitive aging could not differentiate between CN elderly persons with Alzheimer's pathology from CN elderly without it. Given that Alzheimer's pathology is more frequent in CN elderly persons than previously recognized [14,15], is it possible that previous findings that suggested impaired phonological access in "cognitively normal" aging actually pertain to persons with AD pathology, i.e. to preclinical AD [16]?…”
Section: Introductionmentioning
confidence: 99%